The Contribution of Tropical Tuber Crops Towards Food Security - N.M., Nayar (JOURNAL OF ROOT CROPS, 2015)
Tuber crops (with 5.4% energy) are the second most important group of crop plants providing food energy to humans after cereals (49%). Of them, the tropical tuber crops (TTCs) contribute 3.9% of human energy for an average consumption of 28.6 kg capita-1 year-1 (76 kcals capita-1 day-1).Three of the TTCs - cassava, sweet potato and yam - rank among the top 15 crop plants of the world in area under cultivation. Two of the most commonly used terms in development science, Food security and Staple foods, are defined here. The contributions of TTCs to them are highlighted. Cassava and yams are presently among the major crops that show the highest rates of increase in area under cultivation. This may be attributed to their resilience to climate changes. It is proposed that TTCs should double their contribution to food security to 8% by 2030 AD. Towards this, the factors favouring and disfavouring the TTCs are discussed. Moreover additional steps needed to be taken to ameliorate/adapt them are dealt with. These include the present very low yields of TTCs, their low nutritional content, presence of antinutritional factors, high glycaemic index and their prolonged periods of maturity. The ongoing international efforts to mitigate some of them are summarized, including biofortification.